Masting increases seedling recruitment near and far: Predator satiation and improved dispersal in a fleshy‐fruited tree. (22nd June 2022) - Seget, Barbara; Bogdziewicz, Michał; Holeksa, Jan; Ledwoń, Mateusz; Piechnik, Łukasz; Milne‐Rostkowska, Fiona; Kondrat, Katarzyna; Żywiec, Magdalena
Abstract: The animal dispersal hypothesis predicts that mast seeding can increase dispersal rate of seeds by dispersers and enhance reproductive success of plants. However, in contrast to pollination efficiency and predator satiation hypothesis, the animal dispersal hypothesis has received mixed support. Using 12‐year data on fruit production and seedling recruitment of a fleshy‐fruited tree rowan ( Sorbus aucuparia, Rosaceae), we tested if an increase in the fruit production at the population level results in higher proportion of fruits recruiting into seedlings. Recruitment was recorded near (under rowans) and far (under heterospecifics) from conspecifics. Higher recruitment rates under rowans would support predator satiation hypothesis. Higher recruitment rates under heterospecific trees, where fruits can only arrive with animal assistance, would support animal dispersal hypothesis. High population‐level fruit production increased the proportion of fruits recruiting into seedlings both near and far from rowans. In contrast, high individual‐level fruit production did not have a positive effect on the proportion of fruits recruiting into seedlings. Synthesis . Population‐level synchronisation of fruit production is required to generate a more effective plant regeneration. Our findings show that masting enhances seedling recruitment through predator satiation and increased seed dispersal by frugivores. The results provide support for both animal dispersal and predator satiation hypotheses indicating that both mechanisms can operate simultaneously. Abstract : Population‐level synchronisation of fruit production is required to generate a more effective plant regeneration. Our findings show that masting enhances seedling recruitment through predator satiation and increased seed dispersal by frugivores. The results provide support for both animal dispersal and predator satiation hypotheses indicating that both mechanisms can operate simultaneously.